ANALISIS HUBUNGAN KONTROL KEAMANAN, REPUTASI E-VENDOR, KEAKRABAN, DAN PERCEIVED REPUTATION DENGAN KEPERCAYAAN DALAM PENGGUNAAN E-COMMERCE - Nurabiah Nurabiah; Herlina Pusparini; Nurfitriyah Nurfitriyah; Zuhrotul Isnaini; Yusli Mariadi (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2018)
The objective of this study is to examine the security of control, reputation of e-vendor, familiarity and, perceived reputation toward the trust to e-commerce system. This study was conducted in Accounting Department Faculty of Economics and Business Mataram University by targeting online shopping user as research sample. The data used in this study is collected through the distribution of questionnaire with 88 respondents. Data were analyzed by Partial Least Square (PLS). The results of this study indicate that reputation of e-vendor and perceived reputation significantly influence business to trust the e-commerce system. Meanwhile, other variables such as security of control and familiarity do not affect trust on the e-commerce system. This study implies that users to consumer e-commerce systems system needs to be improved both in terms of ease and security in the transaction in order to maximize the system in e-commerce transactions.